1999
DOI: 10.1086/314672
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Epidemiology and Evolution of Epstein‐Barr Virus: Sequence Variation and Genetic Recombination in the Latent Membrane Protein‐1 Gene

Abstract: The phylogeny and evolution of Epstein-Barr virus (EBV) genetic variation are poorly understood. EBV latent membrane protein-1 (LMP-1) gene sequences are especially heterogeneous and may be useful as a tool for EBV genotype identification. Therefore, LMP-1 sequences obtained directly from EBV-infected human tissues were examined by PCR amplification and cloning. EBV genotypes were defined as "strains" from among 22 identified LMP-1 sequence patterns. Three molecular mechanisms were identified by which genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 112 publications
(145 reference statements)
5
121
1
6
Order By: Relevance
“…Similar substitution within the DG-SXXS motif in I B␣ abrogated the ability of I B␣ to recruit ␤-TrCP/HOS (66). Furthermore, substitutions of Ser-366 (such as S366T, S366A, and S366N) are observed more frequently in LMP1 isolates from EBV-associated tumors than in LMP1 from peripheral blood lymphocytes from apparently healthy individuals (30,39,65,67,68). G212S mutation may not be as common as substitution of Ser-366 (65, 67).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar substitution within the DG-SXXS motif in I B␣ abrogated the ability of I B␣ to recruit ␤-TrCP/HOS (66). Furthermore, substitutions of Ser-366 (such as S366T, S366A, and S366N) are observed more frequently in LMP1 isolates from EBV-associated tumors than in LMP1 from peripheral blood lymphocytes from apparently healthy individuals (30,39,65,67,68). G212S mutation may not be as common as substitution of Ser-366 (65, 67).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to 30-bp deletions, these mutations may include D349A substitution (65). Similar substitution within the DG-SXXS motif in I B␣ abrogated the ability of I B␣ to recruit ␤-TrCP/HOS (66).…”
Section: Discussionmentioning
confidence: 99%
“…The association of specific LMP-1 sequences with disease has been extensively studied. Some studies reveal no relationship between specific EBV strains and disease (11,27,50), whereas others have shown that sequence variation in LMP-1 (compared to the B95-8 reference strain) is associated with more oncogenic phenotypes (21-24, 29-31, 44, 49). Thus, the ATGto-ATT/ACC substitution in the LMP-1 gene in tumor-associated strains may not be representative of virus found in healthy individuals.…”
Section: Epstein-barr Virus (Ebv) Is a Human Herpesvirus Well Known Fmentioning
confidence: 99%
“…12 In addition, LMP1-BNLF1 gene polymorphisms, the most discriminating genetic locus, reflect intrastrain diversity. 13,14 EBV primary B-cell infection is polyclonal, always corresponding to an infection by a mixture of different EBV strains regarding the polymorphism of EBNAs and/or LMP1-BNLF1 genes. 15 Hodgkin's lymphoma shows a monoclonal pattern of infection which persists throughout the course of the disease, 16 suggesting that a selection pressure is exerted on the virus during the oncogenic process and raising the question of its role in the pathogenesis of Hodgkin's lymphoma.…”
Section: Introductionmentioning
confidence: 99%